Hy-Brazil, celtic land? A Brief Overview of the Brazilian Irish-Celtic Musical Scene with a Focus on the Rio de Janeiro Case - Santos, Caetano (ABEI Journal, 2023)
The present article charts the appearance and development of an Irish-Celtic (O’Flynn 2014) musical scene in Brazil, a small but tightly knit community of Brazilian amateur and professional musicians and music groups which constitutes a good example of what Mark Slobin named “affinity intercultures” (Slobin 1987). From an ethnomusicological perspective, it seeks to provide a portrait of such social and musical phenomenon based on a tripartite approach: 1) the discussion of international literature on the globalization of Irish traditional music as Celtic music around the turn of the Celtic Tiger period (Williams 2010) and the impacts of such process on Brazil; 2) the presentation and analysis of the results of an online survey conducted in the main Facebook community connected to the scene in order to characterize its main sociodemographic and musical characteristics; 3) the ethnographic description of the Rio de Janeiro chapter of such music scene based on its main musical event, the monthly session known as “Irish Session Rio.”